African guerrillas - Clapham, Christopher S. (Oxford : James Currey ; Kampala : Fountain Publishers ; Bloomington : Indiana University Press, 1998)
This collection of articles and case studies analyze the relationship between African insurgencies and the local societies in which they are set, the organizational principles upon which the insurgencies are based, and the relationship between the insurgencies and the wider world.
Analysing African insurgencies / Christopher Clapham -- Eritrean People's Liberation Front / David Pool -- Tigray People's Liberation Front / John Young -- Sudan People's Liberation Army & the problem of factionalism / Douglas H. Johnson -- Somali armed units : the interplay of political entrepreneurship & clan-based factions / Daniel Compagnon -- Uganda: the National Resistance Army / Pascal Ngoga -- War in Northern Uganda : the Holy Spirit Movements of Alice Lakwena, Severino Lukoya & Joseph Kony (1986-1997) / Heike Behrend -- Rwandan Patriotic Front / Gerard Prunier -- Guerillas in the midst : the Former Government of Rwanda & the Alliance of Democratic Forces for the Liberation of Congo-Zaire in Eastern Zaire / Wm Cyrus Reed -- Liberia's warlord insurgency / Stephen Ellis -- Revolutionary United Front of Sierra Leone : a revolt of the Lumpenproletariat / Ibrahim Abdullah and Patrick Muana.
Includes bibliographical references and index.
Keywords: Since 1900; Insurgency -- Africa, Eastern -- History -- 20th century; Guerrillas -- Africa, Eastern -- History -- 20th century; Insurgency -- Liberia -- History -- 20th century; Guerrillas -- Liberia -- History -- 20th century; Insurgency -- Sierra Leone -- History -- 20th century; Guerrillas -- Sierra Leone -- History -- 20th century; z; z; z; z; z; z; Africa; rebellions; guerrilla warfare; 89.62 political movements; Guerrillas; Insurgency; Politics and government; Bevrijdingsbewegingen; Guerrillabewegingen; Guerrilla warfare -- Africa, East; Insurgency -- Africa, Eastern -- History -- 20th century; East Africa; Guerilla warfare; Liberia; Sierra Leone; Insurgency; History; Africa, Eastern -- Politics and government -- 1960-; Liberia -- Politics and government -- 1980-; Sierra Leone -- Politics and government -- 1961-; Afrique orientale -- Politique et gouvernement -- 1960-; Liberia -- Politique et gouvernement -- 1980-; Sierra Leone -- Politique et gouvernement -- 1961-; Eastern Africa; Liberia; Sierra Leone; Africa, East -- Politics and government; History